Acute Uric Acid Nephropathy following Epileptic Seizures: Case Report and Review - Chinmay Patel; Caitlin P. Wilson; Naveed Ahmed; Yousef Hattab (Case Reports in Nephrology)
Acute hyperuricemia most commonly occurs in patients who experience tumor lysis syndrome. Hyperuricemia along with other electrolyte abnormalities like hyperkalemia, hypocalcemia, and hyperphosphatemia leads to acute kidney injury (AKI) due to acute uric acid nephropathy which is associated with significant morbidity. High risk patients are thus closely monitored for signs of these laboratory abnormalities. Extreme exercise, rhabdomyolysis, and seizures are rare causes of acute hyperuricemia. Serum uric acid level is not routinely monitored as a part of postictal labs. We report an unusual case of AKI in a young male with recurrent seizures and no associated rhabdomyolysis who was found to have acute uric acid nephropathy. Timely administration of Rasburicase prevented the need for dialysis in this patient and led to complete renal recovery. This case illustrates the importance of doing a urine microscopy and checking uric acid level in patients with recurrent seizures who develop unexplainable AKI, as timely management helps improve outcome. We also briefly review the pathophysiology of seizure related hyperuricemia and acute uric acid nephropathy.